A universal reporter cell line for bioactivity evaluation of engineered cytokine products - Jacqueline Mock (Nature Portfolio, 2020)
Abstract Engineered cytokine products represent a growing class of therapeutic proteins which need to be tested for biological activity at various stages of pharmaceutical development. In most cases, dedicated biological assays are established for different products, in a process that can be time-consuming and cumbersome. Here we describe the development and implementation of a universal cell-based reporter system for various classes of immunomodulatory proteins. The novel system capitalizes on the fact that the signaling of various types of pro-inflammatory agents (e.g., cytokines, chemokines, Toll-like receptor agonists) may involve transcriptional activation by NF-κB. Using viral transduction, we generated stably-transformed cell lines of B or T lymphocyte origin and compared the new reporter cell lines with conventional bioassays. The experimental findings with various interleukins and with members of the TNF superfamily revealed that the newly-developed “universal” bioassay method yielded bioactivity data which were comparable to the ones obtained with dedicated conventional methods. The engineered cell lines with reporters for NF-κB were tested with several antibody-cytokine fusions and may be generally useful for the characterization of novel immunomodulatory products. The newly developed methodology also revealed a mechanism for cytokine potentiation, based on the antibody-mediated clustering of TNF superfamily members on tumor-associated extracellular matrix components.